Pengembangan Model Pembelajaran Abad 21 Berbasis Media Penanaman Karakter Bertema Nilai-Nilai Pancasila dan Sadar Konstitusi - Prananta, Yunina Resmi (Jurnal Didaktika Pendidikan Dasar, 2021)
The purpose of this article is to develop a media-based 21st-century learning model in the form of cognitive and affective learning media to cultivate Pancasila values ​​and be aware of the constitution (SIPANCA), test the feasibility and practicality of the media, and measure the effectiveness of the media. The development method is used to refer to the development steps of Gall and Borg (2008) and adopted into five phases. The results of this development are the creation of final media with specifications by affective and cognitive goals, and this media is declared feasible by media experts and field users with high eligibility criteria with an average score of 3,875 out of a total score 4 (3.875/4) for the validation of SIPANCA game; the validation of SIPANCA application (3.75/4); the validation of microcontroller-based SIPANCA shielding media (3.75/4); the practically test of SIPANCA game (3.875/4); the practically test of SIPANCA application (3.975/4); and the practically test of microcontroller-based SIPANCA shielding media (3.93/4). The development of a 21st-century media-based learning model of character with the theme of Pancasila values ​​and awareness of the constitution provides theoretical benefits to the reference of studies in the fields of education, learning, and media development related to learning strategies in schools.